A study of sprint-assisted training for para-swimmers - Tanaka, T.; Yoshimura, Y.; Yasukawa, M.; Oishi, K. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Because the outcomes of swimming races are decided by only fractions of a second, many different training methods have been developed to improve performance. One such training method is sprint-assisted training, commonly used by coaches and competitive swimmers to improve the swimmer`s ability to apply force over a greater distance. However, the most appropriate assist velocity for challenged individuals in para-swimming is unknown. Purpose: To investigate the effects of change in assist velocity for challenged persons in para-swimming. Methods: This study evaluated one female Japanese competitive para-swimmer. The subject has a functional mobility para-swimming classification of "S6" for butterfly. This study used a pulling assist system with a velocity meter (Maglischo, 2003), which includes a wire line to pull the subject. The system precisely recorded intracyclic velocity variations during 25 m of maximum effort, with assist mean velocities of 0.0 m/sec (baseline), 1.1 m/sec (Assisted Speed [AS] 1) and 1.2 m/sec (AS 2), respectively. Results: In stroke phase, minimum velocity was 0.53 ± 0.07 m/sec and maximum velocity was 1.42 ± 0.05 m/sec at baseline. Minimum velocity at AS 1 and AS 2 was 0.81 ± 0.04 m/sec (vs. baseline, t-test, p < .001) and 0.87 ± 0.07 m/sec (vs. baseline, t-test, p < .001), respectively; maximum velocity at AS 1 and AS 2 was 1.38 ± 0.09 m/sec (vs. baseline, t-test, p = 0.142) and 1.57 ± 0.03 m/sec (vs. baseline, t-test, p < .001), respectively. Thus, the minimum velocity (vs. baseline) became larger at AS 1 and AS 2. The maximum velocity (vs baseline) was similar at AS 1, and grew larger at AS 2. Assist velocity AS 1 influenced minimum velocity, and AS 2 influenced both minimum and maximum velocity. Conclusions: Identifying the assist velocity that influences minimum speed is the first step in determining the most appropriate assist velocity. This finding may help to develop optimum assist conditions for training competitive para-swimmers.